2005
DOI: 10.1093/rheumatology/kei045
|View full text |Cite
|
Sign up to set email alerts
|

Low bone density and low serum levels of soluble RANK ligand are associated with severe arterial calcification in patients with Takayasu arteritis

Abstract: Severe arterial calcification in TA is associated with low values of BMD and sRANKL, reinforcing the possible link between bone and vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
2
20
0
4
Order By: Relevance
“…In the present study we found significantly higher VCS in patients who had undergone cardiovascular events. These results were similar to those of Bezerra et al [11], which showed that low serum sRANKL levels were positively associated with severe arterial calcification in patients with Takayasu’s arteritis. In this study we found that cardiovascular events and mortality are significantly higher in patients with low serum sRANKL levels.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we found significantly higher VCS in patients who had undergone cardiovascular events. These results were similar to those of Bezerra et al [11], which showed that low serum sRANKL levels were positively associated with severe arterial calcification in patients with Takayasu’s arteritis. In this study we found that cardiovascular events and mortality are significantly higher in patients with low serum sRANKL levels.…”
Section: Discussionsupporting
confidence: 92%
“…92,93 Vascular calcification and calciphylaxis rarely are associated with malignancy. [94][95][96] " Unknown Gain Gain Chronic inflammation 30 " " " Loss Gain Interleukin 1 [31][32][33] " " " Loss Gain Tumor necrosis factor-a 34 The mechanisms for malignancy-associated hypercalcemia and metastatic calcification are variable but include: (1) tumor production of PTH or PTH-related peptide, vitamin D, or various cytokines; (2) upregulation of RANKL; (3) down-regulation of OPG; or (4) a combination of up-regulated RANKL and downregulated OPG. [97][98][99][100][101][102][103][104][105] Like other diseases that are associated with extraosseous mineral deposition, these cancers may be associated with simultaneous osseous mineral loss.…”
Section: Malignancy Hypercalcemia and Extraosseous Mineralizationmentioning
confidence: 99%
“…Ramsey-Goldman and Manzi (18) reported an association between osteoporosis and cardiovascular disease in patients with a diagnosis of systemic lupus erythematosus. Bezerra et al (19), studying 30 premenopausal women with Takayasu arteritis, demonstrated an association between low-bone mineral density values and the severity of arterial calcification, a finding that contributed to the idea of an association between bone metabolism and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 96%